Efektivitas Putusan Arbitrase dalam Penyelesaian Sengketa Bisnis di Indonesia - Muhammad Alief Nur; Rahma Kuvita Wulandari; Nur Qoilun (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the effectiveness of arbitration as a mechanism for resolving business disputes in Indonesia by focusing on two main aspects: the role of arbitral institutions in providing a dispute resolution process that is fast, efficient, and confidential, and the practical effectiveness of arbitral awards in their implementation. The research is grounded in the increasing complexity of business transactions, which has created a strong need for alternative dispute resolution methods outside the court system. Using a normative juridical approach supported by empirical insights, this study analyzes the advantages of arbitration compared to litigation, including flexibility in the selection of arbitrators, confidentiality of proceedings, and the final and binding nature of arbitral awards. However, the effectiveness of arbitration still faces several challenges, particularly in the enforcement of awards and the annulment mechanism as regulated under Articles 70–73 of Law Number 30 of 1999. While annulment serves as state control to prevent injustice, it may also affect business actors’ confidence in arbitration. This study concludes that although arbitration offers significant advantages, strengthening regulations, improving arbitrator competence, and ensuring judicial consistency in enforcement and annulment processes are crucial to enhancing the effectiveness of business dispute resolution through arbitration in Indonesia.